Género y pobreza: una aproximación a las recuperadoras de residuos de San Francisco (Córdoba - Argentina) - Vergara Mattar, Gabriela (Nómadas. Critical Journal of Social and Juridical Science, 2008)
The process of deterioration of the labour market in the last decades in Argentina, it has returned visible to the recollectors of recyclable materials, who constitute daily figures of the urban landscape registering in really ’ business of the garbage ’. In this work there are analyzed 32 constructed interviews to men and women of San Francisco (Córdoba, Argentina) from which it proposes: 1) to characterize the living and work conditions of this group, 2) to identify the perceptions with regard to the circumstances in which they began with the classification of residues, where the differences between genres are outlined, 3) to show some modalities of a social and sexual division of the work, from a) the organization of the work in the street; b) the importance of the cleanliness in the places of the home where there is realized the storage of the recovered materials and, c) the definition of ’housewife’ like non-work. Finally one will affirm that a Sociology of the bodies can be capable of recovering the experiences of the practices of genre, to be able to realize of the materiality of the inequality and of the manners in which the relations of conflict and power, body is done.